HERMENEUTICS OF THE QUR'AN: A STUDY OF MUHAMMAD SYAHRUR'S THOUGHTS ON THE MEN AND WOMEN EQUALITY - Khasanah, Nur; Hamzani, Achmad Irwan; Aravik, Havis (Universitas Islam Negeri Raden Fatah Palembang, 2020)
This article discussed The Qur'an hermeneutics; Study of Muhammad Syahrur's thoughts on the of men and women equality. The study aimed to find out more about the concept of men and women equality in Muhammad Syahrur's hermeneutics. This article used a literature approach (Library Research) by describing and analyzing research objects, namely reading and analyzing various sources related to the topic, for later being analyzed and finally drawing conclusions and being formulated in a written report. The results showed that Muhammad Syahrur is one of the Islamic thinkers who used a hermeneutic approach in interpreting the Qur'an, especially on fundamental themes such as equality between men and women. In this scope, Syahrur saw a methodological error and there is no revolutionary interpretation of Islamic laws relating to women to be the culprit of gender inequality. Therefore, Syahrur made a legal breakthrough through hermeneutics studies and succeeded in proving that there is no gender bias in Islam.. Keywords: Muhammad Syahrur, Gender, Hermeneutics